2018
DOI: 10.5897/ijnm2018.0303
|View full text |Cite
|
Sign up to set email alerts
|

Success of labour induction institution based cross-sectional study Wolaita Sodo, South Ethiopia

Abstract: There are a number of pregnancy complications that confer significant risk to the mother or fetus. Induction of labour is as an artificial termination of pregnancy utilized to decrease both maternal and neonatal morbidity and mortality. Institution based retrospective cross-sectional study was conducted among 347 pregnant women undergone induction of labour from 2013-2015 in Otona referral hospital. Nearly 207 (59.7%) of the women who undergone through induction of labor procedure had successful delivery of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
2
3
1
Order By: Relevance
“…Thus, the likelihood of failed IOL was more than three times higher among mothers who had unfavorable cervical status compared to their counterparts. This finding is in line with previous literature’s report from Woliata Soda teaching hospital, Ethiopia, 22 France, 37 and Le Scotte Siena Hospital of Italy. 17 It is also supported by another study conducted in Addis Ababa Army referral Hospital, 38 in which a higher proportion of failed induction was observed in mothers with lower Bishop scores.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, the likelihood of failed IOL was more than three times higher among mothers who had unfavorable cervical status compared to their counterparts. This finding is in line with previous literature’s report from Woliata Soda teaching hospital, Ethiopia, 22 France, 37 and Le Scotte Siena Hospital of Italy. 17 It is also supported by another study conducted in Addis Ababa Army referral Hospital, 38 in which a higher proportion of failed induction was observed in mothers with lower Bishop scores.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the overall magnitude of failed IOL among women who underwent IOL in AHMC was found to be 29.6%, and the most common indication for labor induction was PROM (46.4%). This current proportion of IOL is nearly comparable to previous research reports like 26.5% in Wolaita Sodo teaching hospital, Southern Ethiopia, 22 32.3% in Nigeria, 33 25.4% in Addis Ababa, 9 and 28% in Portugal. 34 However, the proportion of failed IOL reported in this study was higher compared to previous studies conducted in different parts of Ethiopia like 21.4% in Jimma University Hospital, 8 Dessie Referral Hospital (19.7%), 7 and Hawassa public health facilities (17.%3), Ethiopia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Induction of labor can use a variety of methods, pharmacological and non-pharmacological [ 1 , 4 ]. Cervical ripening agents, artificial rupture of membranes, and uterine stimulation with oxytocin are all methods for inducing labor [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that IOL is an essential practice in preventing neonatal and maternal mortality and morbidity, it is not always successful and can have unfavorable results. A review of the literature showed that, among women who had IOL, only 84% of mothers in Saudi Arabia [ 12 ], 80.6% in India [ 13 ], 75.9% in Nigeria [ 14 ], and 59.7% in Ethiopia [ 5 ] achieved a vaginal delivery. Maternal age [ 15 , 16 ], place of residence [ 17 ], body mass index (BMI) [ 12 , 18 ], Parity [ 12 , 18 ], [ 17 , 19 , 20 ], gestational age (GA) [ 12 , 17 , 18 ], Bishop score [ 12 , 18 – 21 ], APGAR score [ 12 , 22 ], fetal heart rate pattern [ 17 ], indications [ 13 , 18 , 23 ], hypertensive disorder[ 24 ] and methods of induction [ 17 , 24 , 25 ] were factors associated with the success of labor induction.…”
Section: Introductionmentioning
confidence: 99%